Recommendations for the processing and storage of water samples before polymerase chain reaction (PCR) analysis - BJ Gilpin; M Devane; F Nourozi; B Robson; P Scholes; S Lin (New Zealand Journal of Marine and Freshwater Research, 2013)
A range of options for the storage and partial processing of water samples before polymerase chain reaction (PCR) analysis were evaluated. In addition, temporal storage of extracted DNA at 4 °C was investigated. Filtering the water sample and then storing that filter at −20 °C for up to six months before DNA extraction was equivalent to extracting DNA immediately. Freezing a water sample resulted in an immediate 1 log loss of PCR signal, although thereafter the sample was stable for at least three months. A rapid loss of detectable PCR product was found when storing a water sample at 4 °C for longer than one week. Extracted DNA could be stored at 4 °C for at least six months without considerable loss of PCR signal.

Faecal indicators and pathogens in selected New Zealand waterfowl - EM Moriarty; N Karki; M Mackenzie; LW Sinton; DR Wood; BJ Gilpin (New Zealand Journal of Marine and Freshwater Research, 2011)
Freshly excreted droppings from Canada geese ( n =80), black swans ( n =80), ducks ( n =80) and gulls ( n =80) were collected from sites around New Zealand. The droppings were enumerated for Escherichia coli , enterococci and Salmonella spp., and for the presence/absence of Cryptosporidium spp. Overall prevalence of E . coli and enterococci in samples was 95% and 94%, respectively. Cryptosporidium spp. was detected in 2% of the samples, whereas no Salmonella spp. were detected in the survey. Preliminary estimates of daily microbial outputs suggest that ducks will produce the highest loadings of E . coli and enterococci per bird, whereas Canada geese will produce the highest loadings of Campylobacter spp. per bird. This study provides the first set of indicator and pathogen counts for one of the largest sources of diffuse faecal contamination of natural waters in New Zealand.